ONLINE MARKETING STRATEGIES IN INCREASING SALES (CASE STUDY TOKO RUMAH KURMA & SNACK SIDRAP DI PANGKAJENE KABUPATEN SIDENRENG RAPPANG) - N, Safriyanti; Herman, Bahtiar; Rusdi, Muhammad (Jurnal Ilmiah Ekonomi Dan Bisnis, 2024)
Online marketing has become a very important tool for businesses in various sectors, including the culinary industry. With easy access and wide reach, online marketing offers great opportunities to increase sales. However, with so many competitors in the market, it is important to have an effective marketing strategy. The object of this research is Toko Rumah Kurma & Snack Sidrap, which is a business that operates in the field of buying and selling various dates and various snacks. The aim of this research is to understand contextual conditions with the aim of obtaining a detailed and in-depth picture of the conditions of the natural environment, relative to what is actually happening outside based on what is happening in the study area. The central problem in this research concerns the obstacles faced in the process of implementing and developing sales activities with online marketing strategies. This type of research uses qualitative methods with a case study approach. The data sources used are primary data from interviews, as well as secondary data in the form of documents, diaries, etc. The analytical tool used is SWOT analysis. The research results show that online marketing is effective in increasing sales and through SWOT analysis there are strategic options for increasing sales.